The Effects of Extra Virgin Olive Oil on Alanine Aminotransferase, Aspartate Aminotransferase, and Ultrasonographic Indices of Hepatic Steatosis in Nonalcoholic Fatty Liver Disease Patients Undergoing Low Calorie Diet - Farzad Shidfar; Samaneh Sadat Bahrololumi; Saeid Doaei; Assieh Mohammadzadeh; Maryam Gholamalizadeh; Ali Mohammadimanesh (Canadian Journal of Gastroenterology and Hepatology, 2018)
Background. Coronary artery disease is the most common cause of death in the patients with nonalcoholic fatty liver disease (NAFLD). Studies have shown that there is a strong relation between the increase in the aminotransferase levels and fat accumulation in the liver with cardiovascular complications, independent of all aspects of the metabolic syndrome. This study aimed to examine the effect of virgin olive oil on alanine aminotransferase (ALT) and aspartate aminotransferase (AST) and the severity of steatosis in the NAFLD patients undergoing a weight-loss diet. Methods. This clinical trial was carried out on 50 patients with nonalcoholic fatty liver (mean age of 45.91 ± 9.61 years, mean BMI of 29.7 ± 0.58 Kg/m2) and the subjects were randomly assigned to the olive oil group (receiving the equivalent of 20% of their total daily energy requirement from olive oil) or the control group (with normal consumption of oil) for 12 weeks. All the patients received a hypocaloric diet during the study. At the beginning and the end of the study, the serum levels of ALT and AST and liver steatosis were measured. Findings. A significant decrease in the level of ALT enzymes was observed in the control group at the end of the study (P = 0.004). In the olive oil group, both enzymes decreased compared to baseline measurements (P<0.01). There were significant differences in the ALT and AST levels between the two groups (P<0.02). The severity of liver steatosis did not change significantly during the study. Conclusion. The consumption of a low calorie diet enriched with olive oil, along with slight weight reduction, reinforces the desired effects of weight loss in improving the levels of the hepatic enzymes.